Penerapan Model UTAUT pada Penggunaan E-SKP Pegawai Kecamatan di Nagan Raya - Haris, M. Iqmal; Rusdi, Rusdi; Zhafira, Nabila Hilmy; Hidayat, Muhammad Rahmat (Universitas Teuku Umar, 2024)
district employees in Nagan Raya Regency using the Unified Theory of Acceptance and Use of Technology (UTAUT). The sample of this study was 354 sub-district employees who filled out the research questionnaire. Data were analyzed using the Ordinary Least Square (OLS) method to test the effect of independent variables on the dependent variable. The results showed that performance expectancy, effort expectancy, social influence, and facilitating conditions had a significant effect on behavioral intention to use e-SKP. Performance expectancy was the strongest predictor, followed by social influence, facilitating conditions, and effort expectancy. In addition, behavioral intention had a significant effect on the use behavior of e-SKP. The findings of this study confirm the Unified Theory of Acceptance and Use of Technology (UTAUT) model in the context of implementing e-SKP on sub-district employees in Nagan Raya Regency. The implication is that Performance expectancy Effort expectancy moderated by gender, Social influence moderated by gender, age, experience and voluntariness of use affect behavioral intention. Furthermore, facilitating conditions moderated by age and experience and behavioral intention influence use behavior.Kata kunci: UTAUT, e-SKP, performance expectancy, effort expectancy, social influence, facilitating conditions, behavioral intention, use behavior.